VASCULAR: Inhibition of myogenic tone in rat cremaster and cerebral arteries by SKA-31, an activator of endothelial KCa2.3 and KCa3.1 channels - Mishra, Ramesh C (J Cardiovasc Pharmacol, 2015)
Endothelial KCa2.3 and KCa3.1 channels contribute to the regulation of myogenic tone in resistance arteries by Ca(2+)-mobilizing, vasodilatory hormones. To define further the functional role of these channels in distinct vascular beds, we have examined the vasodilatory actions of the KCa channel activator SKA-31 in myogenically active, rat cremaster and middle cerebral arteries. Vessels pressurized to 70 mmHg constricted by 80–100 microns (i.e. 25–45% of maximal diameter). SKA-31 (10 μM) inhibited myogenic tone by 80% in cremaster and ~65% in middle cerebral arteries, with IC(50) values of ~2 μM in both vessels. These vasodilatory effects were largely prevented by the KCa2.3 blocker UCL1684 and the KCa3.1 blocker TRAM-34 and abolished by endothelial denudation. Pre-incubation with N(G) nitro L-arginine methyl ester (L-NAME, 0.1 mM) did not affect the inhibitory response to SKA-31, but attenuated the ACh-evoked dilation by ~45%. Penitrem-A, a blocker of BK(Ca) channels, did not alter SKA-31 evoked vasodilation, but did reduce the inhibition of myogenic tone by ACh, the BK(Ca) channel activator NS1619 and sodium nitroprusside. Collectively, these data demonstrate that SKA-31 produces robust inhibition of myogenic tone in resistance arteries isolated from distinct vascular beds in an endothelium-dependent manner.